Four Cases with Peripheral Trauma Induced Involuntary Movements - Eun Joo Chung (Journal of Movement Disorders, 2010)
Background and Purpose Although peripheral trauma induced movement disorders have been rarely reported, diagnostic criteria for peripherally induced movement disorders (PIMD) have been established. Because preexisting subclinical movement disorders, or secondary gain for compensation and legal purposes are difficult to confirm, differential diagnosis for physicians still remains difficult. Case Reports We present four patients developed movement disorders after relatively various intervals after traffic accident. Three patients of them showed tremor and one patient presented propriospinal myoclonus. In this report, we investigate whether peripheral trauma can lead to movement disorders and describe the relationship between peripheral injury and movement disorders in four cases. Conclusions Injury was serious enough to develop involuntary abnormal movements with pain and the latency between injury and the onset of movements in all of cases was less than 1 year. Thus, our cases showed temporal and anatomical correlation between injury and the onset of movement disorder, strongly supporting the cause-and-effect relationship by previous diagnostic criteria for peripherally induced movement disorders.